PERHITUNGAN POTENSI BAHAN TAMBANG SIRTU DI WILAYAH SUNGAI DI KABUPATEN PEKALONGAN - Najib, Najib (TEKNIK, 2009)
Pekalongan Residence has a relatively many sand and gravel deposits particularly in river area. Nowadays,many locations have been exploited by local residences or investors from other regions. Even though theexploitation has running, up to now the local government doesn’t know yet how many reserve indicationmaterial deposits in that area. As the result of that condition, it is called for the research to determine thepotential of mining resources in river area. The factors estimate the mining potential based on geologicconditions such as elevation and deposit types. This research use grid and trapezium method. Based onlaboratories tests showed that the dominant materials in that area is up to sand size(around 87 – 98%). Thepotential of deposits is divided into three i.e. river part, levee part and land part. The total of potential in eachdistrict are Kesesi (515.625 m3), Kajen (78.295m3), Karanganyar (1.938.751m3), Wonopringgo( 1.334.375 m3),Doro( 1.984.375 m3), Talun( 1.355.625 m3), Karangdadap( 140.150 m3) and Kedungwuni( 130.000 m3).